Rapid thermal annealing effect of transparent ITO source and drain electrode for transparent thin film transistors. Issue 3 (1st February 2021) - Park, Jin-Hyeok; Seok, Hae-Jun; Jung, Sung Hyeon; Cho, Hyung Koun; Kim, Han-Ki
Abstract: We investigated the rapid thermal annealing (RTA) sequence effect on the electrical, optical, morphological, and structural properties of transparent thin film transistors (TTFTs) with an indium gallium zinc oxide (IGZO) channel and an indium tin oxide (ITO) source/drain. The electrical and optical properties of the IGZO channel and the ITO source/drain electrodes were compared as a function of RTA temperature in ambient air. The performance of a TTFT with only an RTA-processed IGZO channel was compared with that of a TTFT with an RTA-processed IGZO channel and ITO source/drain electrodes. Using the circular transmission line measurement (CTLM) method, we suggest a possible mechanism that explains the effect of the RTA process on the performance of the TTFT with only an annealed IGZO channel vs. that with an annealed IGZO/ITO multilayer. The TTFT with an RTA-processed IGZO/ITO multilayer showed a threshold voltage shift, an improved on/off ratio of 3.54 × 10 11, a subthreshold swing of 0.33 V/decade, and a high mobility of 8.69 cm 2 /V·s. This indicates that simultaneous RTA processing for an IGZO channel and an ITO electrode is beneficial for the fabrication of high-performance TTFTs.